Global Profile of tRNA-Derived Small RNAs in Pathological Cardiac Hypertrophy Plasma and Identification of tRF-21-NB8PLML3E as a New Hypertrophy Marker - Jingyi Xu; Buyun Qian; Feng Wang; Ying Huang; Xinxin Yan; Ping Li; Qian Zhang; Yuan Li; Kangyun Sun (Diagnostics, 2023)
Background: It remains unclear whether transfer RNA-derived small RNAs (tsRNAs) play a role in pathological cardiac hypertrophy (PCH). We aimed to clarify the expression profile of tsRNAs and disclose their relationship with the clinical phenotype of PCH and the putative role. Methods: Small RNA sequencing was performed on the plasma of PCH patients and healthy volunteers. In the larger sample size and angiotensin II (Ang II)-stimulated H9c2 cells, the data were validated by real-time qPCR. Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) were examined in Ang II-stimulated H9c2 cells. The potential role of tsRNAs in the pathogenesis of PCH was explored by bioinformatics analysis. Results: A total of 4185 differentially expressed tsRNAs were identified, of which four and five tsRNAs were observed to be significantly upregulated and downregulated, respectively. Of the five downregulated tsRNAs, four were verified to be significantly downregulated in the larger sample group, including tRF-30-3JVIJMRPFQ5D, tRF-16-R29P4PE, tRF-21-NB8PLML3E, and tRF-21-SWRYVMMV0, and the AUC values for diagnosis of concentric hypertrophy were 0.7893, 0.7825, 0.8475, and 0.8825, respectively. The four downregulated tsRNAs were negatively correlated with the left ventricular posterior wall dimensions in PCH patients (r = −0.4227; r = −0.4517; r = −0.5567; r = −0.4223). The levels of ANP and BNP, as well as cell size, were decreased in Ang II–stimulated H9c2 cells with 21-NB8PLML3E mimic transfection. Bioinformatics analysis revealed that the target genes of tRF-21-NB8PLML3E were mainly enriched in the metabolic pathway and involved in the regulation of ribosomes. Conclusions: The plasma tRF-21-NB8PLML3E might be considered as a biomarker and offers early screening potential in patients with PCH.